The Role of Local Culture in Preventing Radicalism and Intolerance through the Nyadran Tradition - Solechan Solechan (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This research has two main objectives, namely describing the implementation of the Nyadran tradition and analyzing its implications in preventing radicalism and intolerance in Sirkandi Village, Banjarnegara Regency. The Nyadran tradition is carried out before the month of Ramadan, precisely in the month of Sha'ban, and these activities take place in village cemeteries and local mosques. This tradition is the result of harmonious acculturation between Javanese culture and Islamic teachings. In its implementation, Nyadran involves various activities, such as visiting graves, praying together, cleaning graves, and sharing food, to strengthen social ties and maintain the values ??of togetherness in society. The implications of the Nyadran tradition are very significant, especially in maintaining social stability and preventing the emergence of radicalism and intolerance. By encouraging healthy and inclusive social interactions, Nyadran helps create a safe and harmonious environment. This tradition also strengthens the values ??of multiculturalism, contributing to the creation of social harmony not only at the local level but also more broadly, both at the national and global levels. Nyadran is not just a cultural ritual but also plays a vital role in building a tolerant and respectful society